Malaysian Undergraduates Financial Literacy and Financial Education: a Study in Universiti Utara Malaysia - Murugiah, Logasvathi; ., .; ., . (International Journal of Engineering and Technology, 2018)
Financial literacy is becoming increasingly important not only for investors but also for individual in planning his or her day to day budget. Hence, recent development in financial education has highlighted the increasingly important to be financial healthy. Hence, the objectives of this study are (i) to investigate the level of UUM undergraduates’ in financial literacy and (ii) to assess UUM undergraduates’ preferable method in learning financial education. Questionnaires were distributed to 400 undergraduate in UUM, age ranging 20 to 28 years old in 2017. The finding of this study revealed that female have a better saving knowledge compare to male respondents. Furthermore, this study concluded that first year undergraduate’s saving knowledge is slightly better. Meanwhile, final year undergraduates are better in spending and budgeting knowledge. Besides, business programme undergraduate showcase a good financial literacy knowledge. This study also find that preference method in learning financial knowledge are website / internet / online followed by workshop / seminar / talks / conferences and finally social network / social media. Meanwhile, preferable personal financial topic that undergraduate would like to enroll and learn are budget planning or expenses management, followed by debt management and lastly about insurance.